Environment, Social, and Governance Performance and Firm Risk : A Study of the Indian Consumer Goods Sector - Gupta, Khushboo; Raman, T. V.; Deol, O. S.; Gupta, Kanishka (Indian Journal of Finance, 2022)
The objective of the present study was to find the impact of environment, social, and governance (ESG) performance on market measures of risk of Indian consumer goods companies. Mann – Whitney U test was used to compare the risk of companies with high ESG scores and low ESG scores. Ordinary least squares regression was used to find the impact of ESG on systematic, unsystematic, and total risk. Mann – Whitney U test showed that the firms with high ESG scores had lower total and unsystematic risk. The difference in systematic risk of high ESG and low ESG firms was insignificant. The regression results showed that systematic, unsystematic, and total risk was negatively related to the composite ESG score. Individual environment and the social and governance scores showed a negative association with total and unsystematic risk, but only social performance showed a negative association with systematic risk. In a nutshell, superior ESG performance reduced the risk of Indian consumer goods companies and helped increase shareholders’ wealth. Thus, ESG should be considered important by the companies, and they should proactively undertake activities that are responsible to all stakeholders.